Comparative study of a novel plasmid-mediated beta-lactamase, CAZ-2, and the CTX-1 and CAZ-1 enzymes conferring resistance to broad-spectrum cephalosporins. - Chanal, C M (1988)
Infections caused by strains of Klebsiella pneumoniae resistant to broad-spectrum cephalosporins have been observed recently in hospitals in Clermont-Ferrand, France. beta-Lactam resistance resulted primarily from the plasmid-mediated, expanded-spectrum CTX-1 beta-lactamase. Furthermore, since 1987 some K. pneumoniae isolates more resistant to ceftazidime than to other cephalosporins have been observed. This new resistance phenotype was the result of the production of ceftazidimase CAZ-1 and, more recently, CAZ-2. As in CTX-1-producing strains, resistance to beta-lactams resulting from CAZ-2 was associated with resistance to aminoglycosides except gentamicin, sulfonamide, and tetracycline and was transferable to Escherichia coli by conjugation. Agarose gel electrophoresis of plasmid DNA from wild-type strains and transconjugants indicated that CAZ-2 production was mediated by a plasmid of 85 kilobases highly related to plasmid pCFF04 coding for CTX-1 beta-lactamase. The isoelectric point, close to 6.0, of this novel enzyme differed from those of CTX-1 and CAZ-1. Like CAZ-1, the CAZ-2 enzyme efficiently hydrolyzed ceftazidime and aztreonam, but as with CTX-1, cefotaxime gave the maximal reaction rate. For each expanded-spectrum beta-lactamase, the activity of broad-spectrum cephalosporins was restored by clavulanic acid or sulbactam.